The trilogy of job stress, motivation, and satisfaction of police officers: Empirical findings from Bangladesh - Rahman, Gazi Minhazur; Shanjabin, Samia (International Journal of Financial, Accounting, and Management, 2022)
Purpose: The purpose of the study was to identify the trilogy of job stress and job motivation on job satisfaction. For this purpose, police officers of Khulna city were investigated accordingly. Research Methodology: The questionnaire is quantitative in nature and a standard questionnaire was followed throughout the research study. The survey was done in police stations of Khulna city and information was taken from 100 officers from sub-inspector to police commissioners. Results: The study found that job stress is negatively related to job satisfaction. Along with this, there is a negative correlation between job stress and job motivation. However, a positive correlation exists between job motivation and job satisfaction. Limitations: The study result is based on the police personnel in Khulna city rather than in other cities in Bangladesh. There are not prevailing the same ratio of male and female which could affect the measurement of findings. Contribution: The study will help government practitioners and policymakers to understand job stress, motivation, and satisfaction of police personnel in Khulna city.